Topological invariants of the complement to arrangements of rational plane curves - Cogolludo-Agustín, José Ignacio (Memoirs of the American Mathematical Society, 2002)
Preliminaries Ring structure of $H^\bullet(\mathbb{P}^2\backslash \mathcal{R}; \mathbb{C})$ Generalized Aomoto complexes Characteristic varieties, local systems and rational arrangements Examples Bibliography.